Review of the perciform fish genus Symphysanodon Bleeker (Symphysanodontidae), with descriptions of three new species, S. mona, S. parini, and S. rhax - Anderson, William D.; Springer, Victor G. (Zootaxa, 2005)
Symphysanodon mona, a new species of perciform fish, is described from a single specimen collected in Mona Passage off the west coast of Puerto Rico. It differs from all other species of Symphysanodon in having fewer gillrakers on the first gill arch (4 or 5 + 19–21 = 24 or 25 total vs. 8–14 + 20–29 = 28–42 total) and, additionally, from the other two Atlantic species of the genus (S. berryi and S. octoactinus) in two other features of gill-arch morphology, viz., in having a ventral branch of the obliquus dorsalis 3 muscle (vs. its absence in the other two species) and in having a posteriorly projecting extension of the cartilaginous lateral end of ceratobranchial 4 (vs. its absence in the other two species; S. berryi has a small accessory cartilage associated with the lateral end of ceratobranchial 4 which may also be present in S. octoactinus). Symphysanodon parini, new species, known from 10 specimens collected over Sala y Gómez Ridge in the eastern South Pacific, can be distinguished from all other species of Symphysanodon, except S. maunaloae from the central and western Pacific, by the following combination of characters: segmented anal-fin rays 7, tubed lateral-line scales 45–50, total gillrakers on first gill arch 31– 34 (9 or 10 + 22–24), sum of lateral-line scales and gillrakers on individual specimens 77–84, depth of body 22.5–24.7 % SL (4.0–4.4 times in SL), length of depressed anal fin 24.8–26.4 % SL, hypurals 1 & 2 autogenous, hypurals 3 & 4 represented by a single plate, and first caudal vertebra without parapophyses. It is distinguished from S. maunaloae by differences in mean numbers of tubed lateral-line scales (mean = 47.89 for S. parini vs. mean = 44.94 for S. maunaloae) and pectoral-fin rays (mean = 16.90 for S. parini vs. mean = 16.13 for S. maunaloae) and by differences in a few morphometric characters. Symphysanodon rhax, new species, known from specimens collected off the Maldive Islands, northern Indian Ocean, is separable from all other species of Symphysanodon, except S. berryi from the Atlantic, by the following combination of characters: segmented rays in the anal fin 7, tubed lateral-line scales 50, gillrakers on the first gill arch 35–38 (10 or 11 + 25–27), sum of lateral-line scales and gillrakers on individual specimens 85–88, depth of body 20.6–24.8 % SL (4.0–4.9 times in SL), length of depressed anal fin 21.8–23.9 % SL, hypurals 1 & 2 autogenous, hypurals 3 & 4 represented by a single plate, and first caudal vertebra without parapophyses. It can be distinguished from S. berryi by its shorter second anal-fin spine and a suite of other morphometric characters. A key to Symphysanodon and a review of the other species of the genus are also presented.